Mental health literacy of school- going adolescents in sub- Saharan Africa: a regional systematic review protocol - Sodi, Tholene; Quarshie, Emmanuel Nii- Boye; Asante, Kwaku Oppong; Makatu, Makonde Radzilani; Makgahlela, Mpsanyana; Nkoana, Shai; Mutambara, Julia (BMJ Publishing Group, 2022)
Introduction: Assessing mental health literacy has implications for the identification and treatment of mental health problems. Adolescents have been identified as a particularly important target group for initiating and improving mental health literacy. However, much of what we know about adolescent mental health literacy comes from high-income countries. This proposed review seeks to synthesise the available published primary evidence from sub-Saharan Africa on the status and measurement of mental health literacy among school-going adolescents. Methods and analysis: We will perform a systematic review reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (PRISMA-2020). We will systematically search selected global databases (EMBASE, PsycINFO, PubMed and MEDLINE) and regional electronic databases (African Index Medicus and African Journals OnLine) up to December 2021 for observational and qualitative studies published in English and French. The standard quality assessment criteria for evaluating primary research papers from a variety of fields (QualSyst criteria) will be used to appraise the methodological quality of the included studies. The Petticrew-Roberts 3-step approach to narrative synthesis will be applied to the included studies. Ethics and dissemination: We will not seek ethical approval from an institutional review board, as this is a systematic review of available and accessible literature. When completed, the full report of this review will be submitted to a journal for peer-reviewed publication; the key findings will be presented at local and international conferences with-partial or full-focus on (adolescent) mental health (literacy). Prospero registration number: CRD42021229011.